Defining and implementing patient-centered care: An umbrella review. Issue 7 (July 2022) - Grover, Sanya; Fitzpatrick, Aoife; Azim, Farah Tabassum; Ariza-Vega, Patrocinio; Bellwood, Paule; Burns, Jane; Burton, Elissa; Fleig, Lena; Clemson, Lindy; Hoppmann, Christiane A.; Madden, Kenneth M.; Price, Morgan; et al.
Highlights: Despite growing recognition of person-centered care (PCC), gaps still exist in its implementation. Our findings identify many elements of PCC, such as individualized care and shared decision making. A universal PCC definition is needed, along with systems-wide clinician empowerment and culture change for implementation. Abstract: Objectives: Patient- or person-centered care (PCC) integrates people's preferences, values, and beliefs into health decision-making. Gaps exist for defining and implementing PCC; therefore, we aimed to identify core elements of PCC and synthesize implementation facilitators and barriers. Methods: We conducted an overview of systematic reviews (umbrella review) and included peer-reviewed literature for adults in community/primary care settings. Two reviewers independently screened at Level 1 and 2, extracted data and appraised the quality of reviews. Three reviewers conducted a thematic analysis, and we present a narrative synthesis of findings. Results: There were 2371 citations screened, and 10 systematic reviews included. We identified 10 PCC definitions with common elements, such as patient empowerment, patient individuality, and a biopsychosocial approach. Implementation factors focused on communication, training healthcare providers, and organizational structure. Conclusions: We provide a synthesis of key PCC elements to include in a future definition, and an overview of elements to consider for implementing PCC into practice. We extend existing literature by identifying clinician empowerment and culture change at the systems-level as two future areas to prioritize to enable routine integration of PCC into practice. Practice implications: Findings may be useful for researchers and or health providers delivering and evaluating PCC.